Search for dark matter annihilation signals from unidentified Fermi-LAT objects with H.E.S.S. - Abdalla, Hassan; Aharonian, F.; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; Barnacka, A.; et al. (The astrophysical journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.